(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
The rapid expansion of RRB has helped in reducing substantially the regional disparities in respect of banking facilities in India. The efforts made by RRB in branch expansion, deposit mobilization, rural development and credit d eployment in weaker section of rural areas are appreciable. RRB successfully achieve its objectives like to take banking to door steps of rural households particularly in banking deprived rural area, to avail easy and cheaper credit to weaker rural section who are dependent on private lenders, to encourage rural savings for productive activities, to generate employment in rural areas and to bring down the cost of purveying credit in rural areas. The increase in the number of NPAs and the problem of recovery has necessitated the need to study the financial performance of RRBs. The main objective is to study the growth-pattern and financial performance of Regional Rural Banks in India. The study conducted is descriptive in nature and data is collected from published annual reports of RBI and NABARD for the period 2006-2012. The study has witnessed positive impact on the financial performance of RRBs due to amalgamation and various other factors.